Disequilibrium Estimates for Consumption Goods Markets in Centrally Planned Economies - Portes, Richard; Winter, David (Review of Economic Studies, 1980)
Richard Portes, David Winter; Disequilibrium Estimates for Consumption Goods Markets in Centrally Planned Economies, The Review of Economic Studies, Volume 47,